Changes in body mass index and health related quality of life from childhood to adolescence. - Williams, J; Canterford, L; Hesketh, K; Hardy, P; Waters, E; Patton, G; Wake, M (2011)
OBJECTIVE: To determine longitudinal relationships between body mass index (BMI) and health-related quality of life (HRQoL) in an adolescent population sample. Design. Data collected in 2000 and 2005 within the Health of Young Victorians longitudinal cohort study. SETTING: Originally a community sample of elementary school students in Victoria, Australia. Follow-up occurred in either secondary schools or individuals homes. PARTICIPANTS: Cohort recruited in 1997 via a random sampling design from Victorian elementary schools. Originally comprising 1 943 children, 1 569 (80.8%) participated in 2000 (wave 2, 8-13 years) and 851 (54%) in 2005 (wave 3, 13-19 years). Main outcome measures. In both waves participants and their parents completed the PedsQL, a 23-item child HRQoL measure, and BMI z-scores and status (non-overweight, overweight or obese) were calculated from measured height and weight. Associations were tested cross-sectionally and longitudinally (linear regression, adjusted for baseline values) RESULTS: A total of 81.6% remained in the same BMI category, while 11.4% and 7.0% moved to higher and lower categories, respectively. Cross-sectional inverse associations between lower PedsQL and higher BMI categories were similar to those for elementary school children. Wave 2 BMI strongly predicted wave 3 BMI and wave 2 PedsQL strongly predicted wave 3 PedsQL. Only parent-reported Total PedsQL score predicted higher subsequent BMI, though this effect was small. Wave 2 BMI did not predict wave 3 PedsQL. CONCLUSIONS: This novel study confirmed previous cross-sectional associations, but did not provide convincing evidence that BMI is causally associated with falling HRQoL or vice versa across the transition from childhood to adolescence.